Best of the best: a comparison of factor models - Ahmed, Shamim; Bu, Ziwen; Tsvetanov, Daniel (Cambridge University Press, 2018)
We compare major factor models and find that the Stambaugh and Yuan (2016) four-factor model is the overall winner in the time-series domain. The Hou, Xue, and Zhang (2015) q-factor model takes second place and the Fama and French (2015) five-factor model and the Barillas and Shanken (2018) six-factor model jointly take third place. But the pairwise cross-sectional R2 and the multiple model comparison tests show that the Hou, Xue, and Zhang (2015) q-factor model, the Fama and French (2015) five-factor and four-factor models, and the Barillas and Shanken (2018) six-factor model take equal first place in the horse race.